IJTIMOIY TARMOQLARDA QO'LLANILAYOTGAN NEOLOGIZMLARNING LINGVISTIK TAHLILI - Ro'ziyeva Zilola Fayzulla qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article carried out a linguistic analysis of neologisms used in social networks. Instagram Facebook, Twitter, and Instagram social media selected 100 neologisms as part of the study, and they were analyzed semantically, grammatically, and pragmatically. The results of the study show that most neologisms are borrowed from English, which are mainly related to the noun and adjective category. At the end of the study, it was noted that the evolution of language on social networks is gaining momentum and contributes to the enrichment of language in the process.